ORGANISING A «SERATA ITALIANA»: A PROJECT-BASED LEARNING EXPERIENCE WITH FLEMISH STUDENTS OF L2 ITALIAN - Elisa De Cristofaro; Irene Cenni; Emma Grootvelt (Italiano LinguaDue)
This article presents the results of a qualitative study analysing the strengths and weaknesses of an innovative Project-Based Learning (PBL) approach to Italian foreign language acquisition, focused on the organisation of a cultural event. The findings are based on a 5-year pilot experience with Flemish university students enrolled in the Italian Public and Business Communication course at Ghent University (Belgium). The participating students were entrusted with the conceptualisation and execution of an Italian-themed benefit event for a non-academic audience, which required seeking support from Italian-speaking sponsors and collaborators, as well as the use of various project management tools. This case study, which examined student portfolios and a questionnaire through Thematic Analysis, demonstrates the success of the applied PBL method in terms of student motivation and creativity, project management skills (collaboration, planning, networking), self-awareness, and a specific set of communication skills. At the same time, the observed level of stress among students suggests that this PBL approach would benefit from a well-balanced focus on both language acquisition and the accomplishment of the perceived purpose, namely, a well-attended, enjoyable, and relevant event. With these considerations, this article contributes to the scholarship on PBL in foreign language acquisition.